Exponential functions through a real-world context - Budinski, Natalija (Open Schools Journal for Open Science, 2020)
The exponential function as a mathematical concept plays an important role in the corpus of mathematical knowledge, but unfortunately students have problems grasping it. Paper exposes examples of exponential function application in a real-world context.